Mitochondrial Ca(2+) Uptake 1 (MICU1) and Mitochondrial Ca(2+) Uniporter (MCU) Contribute to Metabolism-Secretion Coupling in Clonal Pancreatic β-Cells - Alam, Muhammad Rizwan (American Society for Biochemistry and Molecular Biology, 2012)
In pancreatic β-cells, uptake of Ca(2+) into mitochondria facilitates metabolism-secretion coupling by activation of various matrix enzymes, thus facilitating ATP generation by oxidative phosphorylation and, in turn, augmenting insulin release. We employed an siRNA-based approach to evaluate the individual contribution of four proteins that were recently described to be engaged in mitochondrial Ca(2+) sequestration in clonal INS-1 832/13 pancreatic β-cells: the mitochondrial Ca(2+) uptake 1 (MICU1), mitochondrial Ca(2+) uniporter (MCU), uncoupling protein 2 (UCP2), and leucine zipper EF-hand-containing transmembrane protein 1 (LETM1). Using a FRET-based genetically encoded Ca(2+) sensor targeted to mitochondria, we show that a transient knockdown of MICU1 or MCU diminished mitochondrial Ca(2+) uptake upon both intracellular Ca(2+) release and Ca(2+) entry via L-type channels. In contrast, knockdown of UCP2 and LETM1 exclusively reduced mitochondrial Ca(2+) uptake in response to either intracellular Ca(2+) release or Ca(2+) entry, respectively. Therefore, we further investigated the role of MICU1 and MCU in metabolism-secretion coupling. Diminution of MICU1 or MCU reduced mitochondrial Ca(2+) uptake in response to d-glucose, whereas d-glucose-triggered cytosolic Ca(2+) oscillations remained unaffected. Moreover, d-glucose-evoked increases in cytosolic ATP and d-glucose-stimulated insulin secretion were diminished in MICU1- or MCU-silenced cells. Our data highlight the crucial role of MICU1 and MCU in mitochondrial Ca(2+) uptake in pancreatic β-cells and their involvement in the positive feedback required for sustained insulin secretion.